KELIMPAHAN DAN KEANEKARAGAMAN MAKROZOOBENTOS DI BEBERAPA ANAK SUNGAI BATANG LUBUH KECAMATAN RAMBAH KABUPATEN ROKAN HULU - Siti Rahayu; Radith Mahatma; Khairijon ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
This study was conducted to determine the diversityand abundance of macrozoobenthos in the water creeks of Batang Lubuh, Rambah District. The samples of macrozoobenthos had been taken from 5 stations using Eckman grab. Based on theresults, macrozoobenthos which were consisted of 9 species belongs to three classes ie. Gastropoda, Oligochaeta, andInsecta. The average abundance of macrozoobenthos ranged from 45 to1273 Ind/m2. Composition of macrozoobenthos was dominated by Gastropods (75,36%). The hishest abudance was obtained at station I (1408 ind/m2) and the lowest abudance was obtained at station II (45 ind/m2). The highest diversity Index (H’) of macrozoobenthos was found at Station I (1,971) and the lowest was found at Station II (0), mean while the highest dominance Index of macrozoobenthos was found at Station II (1) and the lowest was found at Station I (0.288). The analysis of water physical and chemical indicated thatthe correlation between diversity of macrozoobenthos and turbidity and also orthoposfat was negative, while the other parameters were positive.